COMPARATIVE STUDY OF EFFLEURAGE AND PETRISSAGE MASSAGE ON HEADACHE INTENSITY IN HYPERTENSION - Risdayanti Raharjeng; Aris Citra Wisuda; Raden Surahmat; Mujahidin; Citra Suraya (Institut Citra Internasional, 2026)
Hypertension is frequently accompanied by headache symptoms that may reduce patient comfort and quality of life. Massage therapy is one of the non-pharmacological interventions used to reduce headache intensity in patients with hypertension. This study aimed to analyze the comparative effectiveness of effleurage and petrissage massage techniques on headache intensity among hypertensive patients at Sumaja Makmur Primary Health Center in 2026. This study employed a quasi-experimental design with a pretest–posttest two-group approach. A total of 170 respondents were selected using purposive sampling and divided into an effleurage group (n=85) and a petrissage group (n=85). Headache intensity was measured using the Numeric Rating Scale (NRS) before intervention and 15 minutes after the massage intervention. Data were analyzed using Wilcoxon and Mann–Whitney tests with a significance level of p<0.05. The results showed significant reductions in headache intensity in both groups after intervention (p=0.000). The effleurage group demonstrated greater reductions in headache scores compared with the petrissage group. Comparative analysis also indicated significant differences in effectiveness between the two massage techniques in reducing headache intensity among hypertensive patients (p<0.05). Effleurage and petrissage massage techniques were effective complementary nursing interventions for reducing headache intensity among patients with hypertension. Effleurage massage tended to produce greater reductions in headache intensity compared with petrissage massage.